Peningkatan Kepuasan Kerja Guru Melalui Penguatan Kepemimpinan Visioner Dan Supervisi Akademik - Ramadani, Amirul Hadid; Sumardi, Sumardi; Laihad, Griet Helena (JURNAL MANAJEMEN PENDIDIKAN, 2024)
IMPROVING TEACHER JOB SATISFACTION THROUGH STRENGTHENING VISIONARY LEADERSHIP AND ACADEMIC SUPERVISIONThis research is classified as correlational research, consisting of two independent variables, namely Strengthening Visionary Leadership and Academic Supervision, and one dependent variable, Teacher Job Satisfaction. The total research sample was 147 teachers who were taken randomly using a proportional random sampling technique from 299 teachers from the population. The correlational descriptive method used in this research uses a quantitative approach. This research produces three conclusions: 1) There is a positive and significant relationship between visionary leadership (X1) and teacher job satisfaction (Y), as indicated by the correlation coefficient ry1 of 0.192, and visionary leadership contributes 37% to teacher job satisfaction. 2) There is a positive and significant relationship between academic supervision (X1) and teacher job satisfaction (Y), as indicated by the correlation coefficient ry2 of 0.082, which shows that academic supervision contributes 7% to teacher job satisfaction. 3) There is a positive relationship between visionary leadership (X1) and academic supervision (X2) together with teacher job satisfaction (Y), shown by a correlation of 0.220, which together contribute 40.9% to teacher job satisfaction. Based on these findings, teacher job satisfaction can be increased through visionary leadership and academic supervision. From SITOREM's analysis of the 15 indicators studied, the results were that four indicators were maintained/developed in providing guidance, providing guidance, reacting appropriately to opportunities and threats, salaries, and incentives. Meanwhile, the 11 indicators that are priorities for improvement are 1st Results and follow-up achieved, 2nd Supervision of subordinate performance, 3rd Evaluation of subordinate performance, 4th Taking risks, 5th Formulating a vision,  6th  Motivator for members,  7th  Creative  Action,  8th  Work  Environment,  9th  Promotion,  10th Supervision, 11th Coworker.